2013
DOI: 10.1673/031.013.15801
|View full text |Cite
|
Sign up to set email alerts
|

Is the Multicolored Asian Ladybeetle,Harmonia axyridis,the Most Abundant Natural Enemy to Aphids in Agroecosystems?

Abstract: The multicolored Asian ladybeetle, Harmonia axyridis Pallas (Coleoptera: Coccinellidae), was introduced into Western Europe in the late 1990s. Since the late 2000s, this species has been commonly considered one of the most abundant aphid predators in most Western European countries. In spite of the large amount of research on H. axyridis, information concerning its relative abundance in agroecosystems is lacking. This study aims to evaluate the abundance of H. axyridis within the aphidophage community in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In addition, other studies conducted in the same region report a very low density of ladybeetles in 2015, indicating that their abundance was low that year in the region of Gembloux (Fassotte, 2016;. Similar annual variability in ladybeetle abundance is reported in Belgium (Vandereycken et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…In addition, other studies conducted in the same region report a very low density of ladybeetles in 2015, indicating that their abundance was low that year in the region of Gembloux (Fassotte, 2016;. Similar annual variability in ladybeetle abundance is reported in Belgium (Vandereycken et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…There were changes in the abundance of natural enemies in different cultivars through the years as well as among cultivars within a year. There may be different causes like climate (Rotheray and Gilbert, 2011), prey density on different cultivars (Thalji, 2006), insolation, quality of host plants (Alhmedi et al, 2009), and adjacent habitats (Alhmedi et al, 2009;Vandereycken et al, 2013). Straub and Snyder (2006) demonstrated that coccinellids are the key species in a natural enemy guild in organic brassica fields in Canada and cabbage aphid, Brevicoryne brassicae.…”
Section: Resultsmentioning
confidence: 99%
“…Both species occur in trees prior to moving to crops in spring and after harvest in late summer, and in early autumn, they again occupy trees (Honek, , ). They mainly breed in crops (Honek, , ) where they are unlikely to be subject to intensive competition from H. axyridis (Vandereycken et al ., ,b; Honek et al ., ). Very few C. quinquepunctata were recorded on trees during P2 and P3.…”
Section: Discussionmentioning
confidence: 99%